Optimization of Leaf Nitrogen Concentration and Monitoring Time for Sustainable Potato Production in Tropics - Fernandes, Fabiana M. [UNESP]; Soratto, Rogério P. [UNESP]; Sandaña, Patricio; Souza, Emerson F. C.; Yagi, Renato (Springer Nature, 2022)
Crop nitrogen (N) status monitoring is required as a decision-making tool to optimize N management of current potato cultivars (Solanum tuberosum L.). Field experiments were conducted to assess the leaf N concentration (LNC) as a diagnostic tool of the N status of potatoes grown in tropical environments of southeastern Brazil. Treatments consisted of two cultivars (Agata and Electra) and five N managements, which varied in rates (0–320 kg N ha−1) and application timings. The LNC was monitored in the most recently matured leaves from 10 to 59 days after emergence (DAE). Total dry matter (DM) biomass and N uptake at vine killing (~ 85 DAE) and fresh tuber yield were also measured. High variation was observed in total DM biomass (3.53–9.75 Mg ha−1), N uptake (41–224 kg ha−1), and tuber yield (14–61 Mg ha−1), with most of the variations ascribed to N management (60–90%). High variation in LNC (68.0–30.8 g kg−1) was attributed to N management and leaf sampling date. Relative tuber yields were positively related to the LNC values across the potato cycle. The threshold value of LNC to reach 95% of maximum tuber yield linearly decreased from 17 to 59 DAE (i.e., from 283 to 999 cumulative growing degree days after emergence) in both potato cultivars. The reference values of LNC to ensure N sufficiency varied from 63.8 g kg−1 (17 DAE) to 52.6 g kg−1 (59 DAE). These outcomes can guide growers to adjust the supply of N according to potato N requirements up to mid-season, preventing the application of excess N fertilizer.
Keywords: Decision-making tool; Mineral nutrition; N management; N status; Solanum tuberosum